17O MAS NMR studies of oxo-based olefin metathesis catalysts: a critical assessment of signal enhancement methods. Issue 40 (3rd October 2016) - Grekov, D.; Bouhoute, Y.; Del Rosal, I.; Maron, L.; Taoufik, M.; Gauvin, R. M.; Delevoye, L.
Abstract : We assessed the DFS parameters for robust and optimal signal enhancement in 17 O NMR studies of silica-supported catalysts. Abstract : The DFS enhancement method as applied to 17 O MAS NMR was critically assessed, first on NaPO3, a simple binary glass system, and in a second step, on a series of catalysis-related organometallic molecules and materials. The robustness of DFS was investigated for the wide range of anisotropic parameters (quadrupolar coupling and chemical shift anisotropy) encountered in these samples. Emphasis has been put on the variation of signal enhancements with respect to the DFS final sweep frequency, pulse amplitude and pulse duration, while line shape distortion issues were also addressed. Finally, the robustness of DFS enhancement of the 17 O MAS NMR signal is shown through its successful application to silica-supported olefin metathesis catalysts.